THE INFLUENCE OF WORK DISCIPLINE, WORK EXPERIENCE AND WORK MOTIVATION ON EMPLOYEE ACHIEVEMENT IN GOVERNMENT INSTITUTIONS - Tifani Adnisa Geni; Syamsir; Nico Pranata Mulya (RADJA PUBLIKA, 2023)
This research is motivated because of achievements performance Work employees Not yet reach the target or Still belong Enough low as well as not optimal. This study aims to: 1) Analyze the influence of Work on performance Work employees in the environment agency government in Koto Tangah District, Padang City. 2) Analyze influence experience Work to performance Work employees in the environment agency government in Koto Tangah District, Padang City. 3) Analyze the influence of motivation Work to performance Work employees in the environment agency government in the Koto Tangah sub-district, Padang City. 4) Analyze the influence of discipline Work to motivate Work employees within the agency government in Koto Tangah District, Padang City. 5) Analyzing influence experience Work to motivation Work employees in the environment agency government in Koto Tangah District, Padang City. The population in this study is whole the employee on the device Koto Tangah District, Padang City, with a total of 101 employees. The determination technique sample uses a purposive sampling technique with a number specified sample of as many as 81 respondents. Data collection is done by the method of the survey with a questionnaire. The data analysis technique used in this study is analysis descriptive and quantitative. Collected data are primary and secondary data that can be classified as a variable exogenous and endogenous variable. Testing hypothesis in this study using analysis path. Based on the results analysis track is known that: 1) Discipline Work is influential positive and significant to the performance Work environment of the employee in Koto Tangah District, Padang City. 2) Experience Work influential positive and significant to performance Work environment employee Koto Tangah District, Padang City. 3) Motivation Work is influential positive and significant to performance Work environment employee Koto Tangah District, Padang City. 4) Discipline Work is influential positive and significant to motivate Work environment employees in Koto Tangah District, Padang City. 5) Experience Work influential positive and significant to motivation Work environment employee Koto Tangah District, Padang City.